PEMBUATAN VIDEO TUTORIAL UNTUK MENGOPERASIKAN HUMAN RESOURCE INFORMATION SYSTEM (HRIS) DI PT X - Qotrunnada Rizkia Maharani Sabila; Dhindayanti Putri; Kiky D.H. Saraswati (PROSIDING SERINA, 2021)
The development of technology and the internet is currently growing rapidly, many benefits from the existence of these two developments. One of them is to facilitate the process of work carried out in daily life. The use of technology can be implemented in work in the realm of Industrial and Organizational Psychology, in terms of managing Human Resources (HR). One tangible form of the use of technological advances and the internet in industrial and organizational work is a software system called the Human Resource Information System (HRIS). The use of the system aims to make it easier for individuals who work in HR management, in addition to time efficiency, data accuracy and accuracy will also be more pronounced when using HRIS. At PT X, for example, most of the divisions in the PT already use HRIS in work activities, but problems arise when new users are present, namely new employees who are not familiar with the use of HRIS. In addition to PT X only providing guidance in written form, other problems arise when the guidance is difficult to reach for new employees at PT X. Therefore, Community Service Activities (PKM), in the form of video tutorials on the use of HRIS, are carried out so that employees and new users of the HRIS system can more easily understand HRIS learning every step of the way. The target of the PKM implementation is new employees or new HRIS users represented by 3 new employees at PT X as PKM participants. Previously they watched the HRIS input tutorial video together, then were given a pre-test and post- test with a predetermined time limit. The purpose of the two tests is to be able to see the participants' understanding of the HRIS input tutorial video. The results of the two tests showed that all participants had an average increase in understanding of 20 points.